Morality/immorality status of a school of medicine and a public hospital: application of a moralization strategy - Perales, Alberto (2008)
Objective: 1º) To evaluate San Marcos University School of Medicine Faculty professors’ knowledge on ethics, deontology and clinical bioethics; 2º) To identify the most frequent ethical problems in both professor-student relationship and teaching hospitals; 3º) With the results obtained to construct a workshop which, after being validated, could be offered to the whole faculty as a basic course; 4º) To contribute to the institutional moralization by reinforcing the institutional ethos. Setting: School of Medicine, Faculty of Medicine, Universidad Nacional Mayor de San Marcos (UNMSM), Lima, Peru. Methods: For objectives first and second, transversal and descriptive design, with qualitative and quantitative methodologies. Following a pre selected criteria 26 professors and 2 Faculty authorities were selected to be interviewed in depth. Upon the qualitative results a specific questionnaire was constructed and validated. Thereafter it was applied to a professor’s sample selected by means of systematic probability sampling that represented 29% of the whole faculty, 801 professors. For the third objective, a pre-post comparative study was used. For the fourth objective, a validated workshop was applied and afterwards the participants’ satisfaction degree was evaluated. Results: Regarding to objectives first and second, diverse ethical problems were identified in the professorstudent and among the professors relationships; also related to hospital professional practice which were generating inadequate health care models and affecting the medical students’ moral training. Among the quantitative results 59% of professors had never received a formal course on ethics, deontology or bioethics; only 6,3% had received them at post-graduate level; 84% did not adequately know which were the Bioethical principles; 53% did not adequately know the Hospital Ethical Committee’s functions; 58% did not adequately know the Research Ethical Committee’ functions, and 71% did not adequately know the Peruvian College of Physician’s Code of Ethics. Regarding the third objective, the workshop was validated in 2 teaching hospitals (Levene: p= 0,001, and Mann Whitney: p= 0,000) respectively. Regarding objective fourth, the workshop was given to 296 professors. Currently it has been instrumented as a permanent basic training course on ethics and deontology in health and clinical bioethics. Finally, the course was requested by a public hospital to be applied to its whole personnel as an attempt to disminish the serious ethical conflicts that were affecting the institutional ethos. Conclusions: 1) San Marcos University School of Medicine faculty’s deficient knowledge on ethics, deontology and clinical bioethics was verified and subsequently improved. 2) The most important institutional ethical problems were identified. 3) The wokshop constructed upon the results was validated in two teaching hospitals and showed significant statiscal differences in pre and post design. 4) 97% of the professors receiving the course declared to have been helped much and very much. 5) The method was also applied (upon special request) to a public hospital, opening interesting perspectives as a new strategy for institutional moralization and to diminish work stress.